2016
DOI: 10.1007/s11205-016-1331-4
|View full text |Cite
|
Sign up to set email alerts
|

Child and Household Deprivation: A Relationship Beyond Household Socio-demographic Characteristics

Abstract: As recession and financial crisis spread across Europe an increasing number of people are at risk of poverty and social exclusion. Children are more exposed to the risk of poverty and social exclusion than the overall population of the EU. The current climate of economic downturn calls out for an urgent need to break the vicious circle of intergenerational transmission of poverty and social exclusion in order to improve the well-being of children in a systematic and integrated way. Using the EU-SILC 2009 modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Though a few have studied the distribution between parents and children (see e.g. Main and Bradshaw, 2016; Bárcena Martín et al , 2017), most studies focus on the intra‐couple distribution (as we will do below), covering different aspects. Some investigate the ways in which a couple's finances are managed and controlled, while others have studied individual consumption or living standards of wives and husbands within couples (see Bennett, 2013, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Though a few have studied the distribution between parents and children (see e.g. Main and Bradshaw, 2016; Bárcena Martín et al , 2017), most studies focus on the intra‐couple distribution (as we will do below), covering different aspects. Some investigate the ways in which a couple's finances are managed and controlled, while others have studied individual consumption or living standards of wives and husbands within couples (see Bennett, 2013, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these dimensions stands for one of our dependent variables for child deprivation. In general, the majority of studies on European level usually aggregate all the child deprivation items provided by the EU-SILC into one sole variable, which facilitates the interpretation of deprivation as well as comparison between countries, years or collectives (Bárcena-Martín et al., 2017a , b ; Guio et al., 2020 ). Despite this, we have chosen to distinguish between different types of child deprivation, as this allows us to take into account the multidimensional nature of deprivation and to identify areas that may be more affected by the increase of single parenthood amongst women with a lower educational level in Italy and Spain.…”
Section: Data Variables and Methodologymentioning
confidence: 99%
“…Apart from the main explanatory variables, and in a similar way to previous works, we also include a set of control variables (Bárcena-Martín et al., 2017a , b ; Chzhen & Bradshaw, 2012 ). Firstly, we consider some characteristics of parents such as age (classified in four categories according to the age of the household’s oldest parent: older than 50, between 41 and 50, between 31 and 40, and 30 or younger) and country of birth (immigrant and non-immigrant parents).…”
Section: Data Variables and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…(Knies 2011;Rees et al 2011). Currently, studies have revealed that children's perceptions of material deprivation are related with subjective well-being (Bradshaw et al 2017;Bárcena-Martín et al 2017;Main 2018), suggesting that the child-centric method is more effective than the adult-centric method in predicting subjective well-being of children.…”
Section: Introductionmentioning
confidence: 99%